Incidence of Cesarian in Cities that Integrate the 20th Regional Health Coordination of Ceará, in the Period of 2008-2018 - Luís Pereira-; Cicero Pedro da Silva Júnior; Anderson Rennan Pereira Muniz Pinheiro; Andressa de Alencar Silva; Rachel de Sá Barreto Luna Callou Cruz (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Brazil is among the leaders in the ranking of the number of elective cesarean sections, and such a procedure, when unnecessary, can have serious consequences for the health of the mother and the newborn, which is generally not cleared up satisfactorily to the pregnant woman before the procedure. This study aimed to verify the incidence of cesarean sections in cities that integrate the 20th Regional Health Coordination of Ceará (RHCC), in the period of 2008-2018. This is a descriptive and retrospective study, with a quantitative approach, using data from the Hospital Information System of the Unified Health System (HIS/ SUS) of the SUS IT Department (DATASUS). This study demonstrated an increase in the number of cesarean sections in the cities of the 20th RHCC, and sometimes exceeding the number of vaginal deliveries. It is necessary to overcome the medicalization of childbirth, facilitate women's access to health services and encourage the strengthening of educational activities, especially in primary care services, in order to encourage pregnant women to choose vaginal delivery.